Tumor Necrosis Factor Receptor 2 Restricts the Pathogenicity of CD8(+) T Cells in Mice with Colitis - Punit, Shivesh (Gastroenterology, 2015)
BACKGROUND & AIMS: Tumor necrosis factor (TNF) receptor 2 (TNFR2, Tnfrsf1b) regulates multiple aspects of immune function; but little is known about its role in the immunopathogenesis of inflammatory bowel disease (IBD). We investigated whether TNFR2 restricts the activity of specific immune cell subtypes to protect against the development of colitis in mice. METHODS: Tnfr2(−/−) mice were crossed with Il10(−/−) mice, which spontaneously develop colitis, to generate Il10(−/−)Tnfr2(−/−) mice. Colonic tissues were collected from Il10(−/−)Tnfr2(−/−) mice along with Il10(−/−) mice (controls), and analyzed by flow cytometry and histology. Bone marrow was transplanted into Il10(−/−) and Il10(−/−)Tnfr2(−/−) mice from Il10(−/−) or Il10(−/−)Tnfr2(−/−) donors by intravenous injection. CD8(+) T cells were neutralized in Il10(−/−)Tnfr2(−/−) mice by intraperitoneal injection of anti- CD8 or isotype control antibodies. Colitis was induced in Rag2(−/−) mice by intravenous injections of naïve CD8(+) T cells isolated from C57BL/6 or Tnfr2(−/−) mice. RESULTS: Il10(−/−)Tnfr2(−/−) mice spontaneously developed more severe colitis compared to Il10(−/−) controls, characterized by selective expansion of colonic CD8(+) T cells. Transplant of TNFR2- deficient bone marrow resulted in significantly increased incidence and severity of colitis. Transcriptome analyses showed that the expression of genes regulated by TNFR2 were specific to CD8(+) T cells, and included genes associated with risk for IBD. Depletion of CD8(+) T cells from Il10(−/−)Tnfr2(−/−) mice prevented colonic inflammation. Adoptive transfer of TNFR2-null naïve CD8(+) T cells, compared with CD8(+) T cells from control mice, increased the severity of colitis that developed in Rag2(−/−) mice. CONCLUSION: TNFR2 protects mice from colitis by inhibiting the expansion of colonic CD8(+) T cells. TNFR2 regulates expression of genes that regulate CD8(+) T cells and have been associated with susceptibility to IBD. Disruption in TNFR2 signaling might therefore be associated with pathogenesis. Strategies to increase levels or activity of TNFR2, and thereby reduce the activity of CD8(+) T cells, might be developed to treat IBD patients with CD8(+) T cell dysfunction.